Effect of 4 HPPD inhibitors on weeds, growth and yield of pearl millet (Pennisetum glaucum) in a custard apple (Annona squamosa) based agri-horticulture system in Mirzapur, Uttar Pradesh - Sanodiya, Pratik (Indian Journal of Agroforestry, 2026)
This study aimed to explore the effects of different weed management strategies on pearl millet production and its economic viability during the Kharif season of 2023 at Banaras Hindu University, Mirzapur. The experiment was conducted with ten treatments, which included various herbicides and mechanical methods. At 60 days after sowing (DAS), Atrazine 1.0 kg/ha followed by hand weeding (T1) showed the best results, significantly reducing weed density and dry weight compared to other treatments, with the weedy check performing the worst. T1 also resulted in the highest weed control efficiency, panicle length, and grain yield. Other treatments such as Pendimethalin 1.0 kg/ha fb 1 HW (T2) and combinations with Tembotrione 100 g/ha and 2,4-D 0.75 kg/ha also showed good results, though T1 remained the most effective. Economic analysis suggested that T1 offered the best returns, making it a viable option for enhancing pearl millet productivity in this region. The results support informed decision-making for sustainable and efficient crop management in the agro-climatic conditions of eastern Uttar Pradesh.